Disability Inclusive Disaster Risk Reduction and Management: Assessing Vulnerabilities and Local Responses in Maasin City, Philippines - Oraiz, Kristoper Rex; Oraiz, Elmee Joy (Asean Social Work Journal, 2025)
Age and Disability Consortium. (2018). Minimum standards for age and disability inclusion in humanitarian action. https://adstandards.org/ Cabauatan, R. J., Mendoza, A. V., & Torres, M. L. (2021). Disaster preparedness and disability inclusion: Gaps in Philippine evacuation facilities. Philippine Journal of Social Development, 14(2), 55–72. Calumba, S. R., Santiago, J. M., & Ueda, T. (2021). Earthquake evacuation choice and management in a developing archipelagic country—A case study of Surigao City, Philippines. Sustainability, 13(11), 5783. https://doi.org/10.3390/su13115783 Chang, K.-Y. J., Villeneuve, M., Crawford, T., Yen, I., Dominey-Howes, D., & Llewellyn, G. (2023). Disaster preparedness, capabilities, and support needs: The lived experience perspectives of people with disability. Disabilities, 3(4), 648–665. https://doi.org/10.3390/disabilities3040042 Chang, Y., Chen, L., & Wu, Y. (2022). Family caregiving burden in households with multiple members having chronic illnesses or disabilities: A population-based study. Journal of Family Nursing, 28(1), 45–61. https://doi.org/10.1177/10748407211049844 Crawford, T., Chang, K.-Y. J., Nila, F., Subramaniam, P., Bethune, L., Parkinson, D., & Villeneuve, M. (2023). The intersectionality of gender, sexual identity, and disability in disaster risk reduction in OECD countries: A rapid scoping review. Disabilities, 3(4), 562–578. https://doi.org/10.3390/disabilities3040036 Disability Inclusive Disaster Risk Reduction Network. (n.d.). A synthesis of disability-inclusive disaster risk reduction assessments: Findings from seven countries. DIDRRN. https://didrrn.net/resource/a-synthesis-of-disability-inclusive-disaster-risk-reduction-assesments-findings-from-seven-countries/ Gonzalez, M., Santos, R., & Soriano, F. (2022). The resilience of families in emergency evacuation centers: A case study of Typhoon Haiyan survivors in the Philippines. Disaster Prevention and Management, 31(6), 763–779. https://doi.org/10.1108/DPM-12-2021-0463 Handicap International. (2012). Disability inclusive community-based disaster risk management: A toolkit. Handicap International. Harvard Humanitarian Initiative. (2023). Filipino PWDs struggle more in disaster recovery and preparedness. https://hhi.harvard.edu/blog/filipino-pwds-struggle-more-disaster-recovery-and-preparedness Hernandez, L. A., Pineda, R., & Reyes, A. (2021). Strain on family relationships during disasters: A study of displaced families in the Philippines. International Journal of Disaster Risk Reduction, 57, 102191. https://doi.org/10.1016/j.ijdrr.2021.102191 International Labour Organization. (2022). Decent work for persons with disabilities: Promoting rights in the workplace. https://www.ilo.org/global/topics/disability-and-work/lang--en/index.htm Junod, A., Santos, M. J., & Lee, H. (2024). Disability, housing, and disaster vulnerability: A cross-regional analysis. Journal of Environmental Risk and Social Policy, 12(1), 44–59. Kaya, A., & Karanci, A. N. (2023). The experiences of people with disabilities in the 2020 Izmir earthquake: A qualitative study. International Journal of Disaster Risk Reduction, 85, 103548. https://doi.org/10.1016/j.ijdrr.2023.103548 Manalo-Asay, M. (2024). Disability-inclusion in disaster risk reduction management (DRRM) programs of the municipalities in Camarines Norte. International Journal of Innovative Studies, 10(1). https://ijois.com/index.php/ijoisjournal/article/view/192 Nielo, L. C. G. (2024). A disaster communication plan for higher education institutions in the island province of Occidental Mindoro, Philippines. Frontiers in Communication. https://doi.org/10.3389/fcomm.2024.1368221 Philippine Atmospheric, Geophysical and Astronomical Services Administration (PAGASA). (2020). Flood information. https://www.pagasa.dost.gov.ph/flood Philippine Consortium on Social Protection. (n.d.). Promoting self-development and access and participation of persons with disability: A policy brief. https://planinternational.org/uploads/sites/25/2022/03/policy_brief_pwd_final.pdf Philippine Statistics Authority. (2020). 2020 census of population and housing: Population of Maasin City. https://psa.gov.ph/content/2020-census-population-and-housing-population-maasin-city Pinquart, M., & Sörensen, S. (2021). Correlates of caregiver burden: A meta-analysis. The Gerontologist, 61(5), e185–e197. https://doi.org/10.1093/geront/gnaa074 PreventionWeb. (2023). Poverty, inequality and disaster risk: Findings from Southeast Asia. United Nations Office for Disaster Risk Reduction. https://www.preventionweb.net/publication/poverty-inequality-and-disaster-risk-southeast-asia Rappler. (2019, September 1). Coronavirus pandemic exposes gap in evacuation centers in the Philippines. https://www.rappler.com/newsbreak/in-depth/coronavirus-pandemic-exposes-gap-evacuation-centers-philippines/ Republic Act No. 10121. (2010). An act strengthening the Philippine disaster risk reduction and management system, providing for the national disaster risk reduction and management framework and institutionalizing the national disaster risk reduction and management plan. Official Gazette of the Republic of the Philippines. https://www.officialgazette.gov.ph/2010/05/27/republic-act-no-10121/ Republic Act No. 7277. (1992). Magna Carta for disabled persons, as amended by R.A. 9442 and R.A. 10524. Official Gazette of the Republic of the Philippines. https://www.officialgazette.gov.ph/1992/03/24/republic-act-no-7277/ Rofiah, N. H., Kawai, N., & Hayati, E. N. (2024). Disability-inclusive disaster risk reduction in schools: A confirmatory factor analysis. Jàmbá: Journal of Disaster Risk Studies, 16(1), a1559. https://doi.org/10.4102/jamba.v16i1.1559 Setijaningrum, E., Kassim, A., Soeginio, A., & Ariawantara, P. (2024). Beyond tokenism, toward resilience: Furthering a paradigmatic shift in disability-inclusive disaster risk reduction. Cogent Social Sciences, 10(1), 2319376. https://doi.org/10.1080/23311886.2024.2319376 Southern Leyte Provincial Government. (2020). Natural disaster risk profile: Province of Southern Leyte. https://www.scribd.com/document/539335215/Southern-Leyte-Tsunami-3 Sphere Association. (2018). The Sphere handbook: Humanitarian charter and minimum standards in humanitarian response (4th ed.). https://spherestandards.org/handbook Tan, M. L., & Gaillard, J. C. (2023). Disability, communication, and disaster preparedness: Reframing access to information as a rights-based priority. International Journal of Disaster Risk Reduction, 93, 103962. https://doi.org/10.1016/j.ijdrr.2023.103962 Thompson, R., & Dizon, R. A. (2023). Inclusive infrastructure and emergency response: Challenges for persons with disabilities in the Philippines. Journal of Disability and Development, 15(2), 88–103. United Nations. (2006). Convention on the rights of persons with disabilities. https://www.un.org/disabilities/documents/convention/convoptprot-e.pdf United Nations Office for Disaster Risk Reduction. (2015). Sendai Framework for Disaster Risk Reduction 2015–2030. https://www.undrr.org/publication/sendai-framework-disaster-risk-reduction-2015-2030 United Nations Office for Disaster Risk Reduction. (2023). 2023 global survey report on persons with disabilities and disasters. https://www.undrr.org/report/2023-gobal-survey-report-on-persons-with-disabilities-and-disasters Villeneuve, M., Abson, L., Pertiwi, P., & Moss, M. (2021). Applying a person-centered capability framework to inform targeted action on disability-inclusive disaster risk reduction. International Journal of Disaster Risk Reduction, 52, 101979. https://doi.org/10.1016/j.ijdrr.2020.101979 World Health Organization. (2023, March 7). Disability and health. https://www.who.int/news-room/fact-sheets/detail/disability-and-health(World Health Organization (WHO)